"Ihubacter massiliensis": a new bacterium isolated from the human gut. (September 2016) - Ndongo, S.; Lagier, J.-C.; Fournier, P.-E.; Raoult, D.; Khelaifia, S.
Abstract: We report here the main characteristics of " Ihubacter massiliensis, " strain Marseille-P2843 T (CSUR P2843), a new genus of the Clostridiales family isolated from a stool sample from a healthy 29-year-old woman.